Care Coordination Needs of Families of Children with Down Syndrome: A Scoping Review to Inform Development of mHealth Applications for Families - Beth Skelton; Kathleen Knafl; Marcia Van Riper; Louise Fleming; Veronica Swallow (MDPI AG, 2021)
Care coordination is a critical component of health management aimed at linking care providers and health-information-involved care management. Our intent in this scoping review was to identify care coordination needs of families of children with Down syndrome (DS) and the strategies they used to meet those needs, with the goal of contributing to the evidence base for developing interventions by using an mHealth application (mHealth apps) for these families. Using established guidelines for scoping reviews, we searched five databases, yielding 2149 articles. Following abstract and full-text review, we identified 38 articles meeting our inclusion criteria. Studies incorporated varied in regard to research designs, samples, measures, and analytic approaches, with only one testing an intervention by using mHealth apps. Across studies, data came from 4882 families. Common aspects of families' care coordination needs included communication and information needs and utilization of healthcare resources. Additional themes were identified related to individual, family, and healthcare contextual factors. Authors also reported families' recommendations for desirable characteristics of an mHealth apps that addressed the design of a personal health record, meeting age-specific information needs, and ensuring access to up-to-date information. These results will further the development of mHealth apps that are tailored to the needs of families with a child with DS.